INDONESIAâ€™S DEMOCRACY UNDER JOKO â€œJOKOWIâ€ WIDODO LEADERSHIPS: CONSTRUCTING HUMAN RIGHTS IN GLOBALIZATION (2014-2019) - Hendra Manurung (Kajian Asia Pasifik, 2017)
On 20 October 2014, Joko “Jokowi: Widodo was inaugurated as 7th Indonesia President in the Parliament House, Senayan, to lead the world biggest Muslim country for 5 (five) years presidency (2014-2019). President Joko Widodo’s record during his first year in office was mixed. His administration signaled it would more actively defend the rights of beleaguered religious minorities, victimized by both Islamist militants, and discriminatory laws, but made few concrete policy changes. He granted clemency in May 2015 to five of Papua’s political prisoners and released another one in October, but at the same time had not freed the approximately 70 (seventy) Papuans and 29 (twenty nine) Ambones which still imprisoned for peaceful advocacy of independence. He announced lifting of decades-old restrictions on foreign media access to Papua, but then did not follow through, allowing senior government officials to effectively defy the new policy without consequences. While in August 2015, Joko Widodo announced that Jakarta will create a reconciliation commission in addressing human rights violations of the past 50 years and still left out the details (1965-2015). This research attempts to describe analytically how Indonesia Human Rights policy affects and providing solution to overcome national human rights issues. Keywords: minorities, discrimination, human rights, national policy, leaderships Abstrak Pada tanggal 20 Oktober 2014, Joko "Jokowi: Widodo dilantik sebagai Presiden Indonesia ke-7 di Gedung Parlemen, Senayan, untuk memimpin negara Muslim terbesar di dunia selama 5 (lima) tahun kepresidenan (2014-2019). Catatan terkait Presiden Joko Widodo selama tahun pertamanya menjabat beragam. Pemerintahannya mengisyaratkan akan lebih aktif membela hak-hak minoritas agama yang terdiskriminasikan, yang menjadi korban baik oleh militan Islam, dan undang-undang yang diskriminatif, namun hanya sedikit membuat perubahan kebijakan konkret. Dia memberikan grasi pada bulan Mei 2015 kepada lima tahanan politik Papua dan membebaskan satu lagi di bulan Oktober, namun pada saat bersamaan belum membebaskan sekitar 70 (tujuh puluh) orang Papua dan 29 (dua puluh sembilan) warga Ambon yang masih dipenjarakan karena advokasi kemerdekaan secara damai. Dia mengumumkan pencabutan pembatasan akses media asing yang telah berlangsung puluhan tahun ke Papua, namun kemudian tidak menindaklanjuti, yang memungkinkan pejabat pemerintah senior untuk secara efektif menentang kebijakan baru tersebut tanpa konsekuensi. Sementara pada bulan Agustus 2015, Joko Widodo mengumumkan bahwa Jakarta akan membuat komisi rekonsiliasi dalam menangani pelanggaran hak asasi manusia dalam 50 tahun terakhir dan masih mengabaikan rinciannya (1965-2015). Penelitian ini mencoba untuk menggambarkan secara analitis bagaimana kebijakan Hak Asasi Manusia Indonesia mempengaruhi dan memberikan solusi untuk mengatasi masalah hak asasi manusia nasional. Kata Kunci: minoritas, diskriminasi, hak asasi manusia, kebijakan nasional, kepemimpinan